Organizational culture and its relationship to decision-making in faculties of physical education and sports sciences - Mohammed Ahmed Saber (Global Scientific Publishing, 2025)
The study aimed to identify the level of organizational culture and decision-making and to identify the relationship between organizational culture and decision-making from the point of view of the study sample. The study sample was selected by the comprehensive enumeration method and consisted of (95) as the research included assistants and heads of departments in the faculties of physical education and sports sciences in Iraq. The researcher used the survey method from the basic methods in descriptive research because it is appropriate for the nature of the study. The study reached the following results: The results showed a good level for the organizational culture variable, as well as the results showed a good level for the decision-making variable. The results showed a statistically significant relationship between organizational culture and decision-making among the study sample. The researcher recommends the need to pay attention to organizational culture in college administration because it has a positive impact on trust, cooperation, cohesion and creativity among the members of the college, and the need for members to participate in the administrative process in the college in the field of decision-making
Keywords: administrative process; organizational; physical education; study